EXPLORING METACOGNITIVE STRATEGIES FOR ENGLISH READING COMPREHENSION IN ISLAMIC BOARDING JUNIOR HIGH SCHOOL - Siti Tazkiyah; Indah Purnama Dewi (IKIP Siliwangi, 2022)
Reading is one of the important lessons for students, especially when they are learning English. English learners usually can read the text well, but many of them cannot understand the content of the text. Several previous studies found strategies that can help students in reading comprehension, namely metacognitive strategies. However, there has been no research involving English students in Islamic boarding schools, while it is known that there are many boarding schools, especially in Indonesia. Therefore, this article attempts to describe a study that further explores metacognitive strategies for understanding English reading by students in Islamic boarding schools where in several aspects this school is different from public schools. Using a qualitative descriptive design, this study describes the results through reading comprehension tests, MARSI questionnaires and semi-structured interviews. The results showed that students had good awareness in the use of metacognitive reading strategies. However, there is no significant relationship when it comes to reading comprehension results. This is because several other factors such as interest, background knowledge of students and the role of the teacher also have a major influence on students' reading comprehension. Keywords: Metacognitive Strategy, English Reading Comprehension, Islamic Boarding School